The Influence of Social Media Marketing on the Intention to study at Private Universities in Thailand: The Role of Trust and Image - Chandi, Khanaphot; Lexcharoen, Somchai (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This article aims to 1) validate a structural equation model of the intention to study at private universities in Thailand, and 2) analyze the direct and indirect effects of mediating variables on the intention to study at private universities in Thailand, thereby addressing the academic gap regarding digital platform influences which differ from traditional offline contexts. This quantitative research examined social media marketing, image, and trust. Data were collected via online questionnaires from 446 Grade 12, vocational certificate, and high vocational certificate students using convenience sampling. The data were analyzed using descriptive statistics, confirmatory factor analysis, and structural equation modeling. The results revealed that the model fit the empirical data. Image had the highest direct effect, followed by trust, whereas social media marketing had a low direct effect. However, image and trust significantly functioned as partial mediators (variance accounted for of 74.3 percent) with indirect effects of 0.098 and 0.104, respectively. This resulted in a substantial total effect of 0.272 for social media marketing. Consequently, private universities should create relationship-based content on social media to convert perceptions into image and trust, which are the primary mechanisms driving enrollment decisions.